Local irrigation management institutions mediate changes driven by external policy and market pressures in Nepal and Thailand - Ram C. Bastakoti (2018)
This article assesses the role of local institutions in managing irrigation water use. Fifty irrigation systems in each country were studied in Nepal and Thailand to compare the influence of local institutions on performance of irrigation systems amid changes in external policy and market pressures. Nepal's new irrigation policy after the re-instatement of multiparty democracy in 1990 emphasized participatory irrigation management transferring the management responsibility from state authorities to water users. The water user associations of traditional farmer-managed irrigation systems were formally recognized by requiring registration with related state authorities. In Thailand also government policies encouraged people's participation in irrigation management. Today water users are directly involved in management of even some large irrigation systems at the level of tertiary canals. Traditional communal irrigation systems in northern Thailand received support for system infrastructure improvement but have faced increased interference from government. In Thailand market development supported diversification in farming practices resulting in increased areas under high water-demanding commercial crops in the dry season. In contrast, the command areas of most irrigation systems in Nepal include cereal-based subsistence farming with only one-third having commercial farming. Cropping intensities are higher in Nepal than in Thailand reflecting, in part, differences in availability of land and management. In both countries local institutions play an important role in maintaining the performance of irrigation systems as external drivers and local contexts change. Local institutions have provided alternative options for irrigation water use by mediating external pressures. © 2010 Springer Science+Business Media, LLC.